Factors Influencing Entrepreneurship Curriculum and Pedagogy Towards the Development of Graduate Entrepreneurs in South Africa Higher Education - Nwachukwu, Juliet Nwakaego; Iwu, Chux Gervase; Nyandoro , Zivanayi (GILE Journal of Skills Development, 2026)
South Africa continues to face persistently high levels of graduate unemployment, which restricts economic productivity and further intensifies poverty, inequality, and the marginalisation of young people. In response, the development of graduate entrepreneurs has become a strategic national priority, as entrepreneurial skills are increasingly viewed as a pathway to job creation, innovation and inclusive economic growth. Higher education institutions are, therefore, crucial in equipping graduates with the entrepreneurial abilities required to pursue self-employment and venture creation. To understand the reasons for low entrepreneurial intention, this study examines curriculum and pedagogical factors that shape entrepreneurial intentions among university students in South Africa, using a qualitative research design. Findings reveal that entrepreneurship education remains predominantly theoretical, with critical gaps including a lack of early exposure, limited practical learning, misaligned curriculum and pedagogy, poor integration with non-business programmes, systemic constraints, and insufficiently skilled lecturers. The study argues that without meaningful curriculum reform and pedagogical innovation, entrepreneurship education cannot effectively develop graduate entrepreneurs. Recommendations include adopting experiential and problem-based teaching strategies, strengthening industry partnerships, enhancing lecturer capacity and integrating entrepreneurship across all disciplines. These insights inform policy and practice to transform entrepreneurship education into a more effective catalyst for graduate entrepreneurs and ultimately, contribute to South Africa's socio-economic development.